Pharmacokinetics, efficacy and safety of a novel fibrinogen concentrate in pediatric patients with congenital afibrinogenemia. Issue 1 (9th January 2023) - Khayat, Claudia Djambas; Navarro-Puerto, Jordi; Ross, Cecil Reuben; Subramanian, Kannan; Kalappanavar, Nijalingappa K.; Rucker, Karen; Liang, Wei; Mondou, Elsa
Abstract : Introduction: Congenital afibrinogenemia treatment with plasma-derived fibrinogen concentrates in pediatric patients is limited. This study investigated the pharmacokinetics, surrogate efficacy, and safety of a plasma-derived fibrinogen concentrate (FIB Grifols) in pediatric patients with congenital afibrinogenemia. Methods: Patients aged <18 years old diagnosed with congenital afibrinogenemia were included in this prospective, multinational, phase 1–2, single-arm study. After a single dose of a plasma-derived fibrinogen concentrate (70 mg/kg body weight), pharmacokinetic parameters were determined from plasma fibrinogen activity (Clauss method) and antigen method (ELISA), and calculated by noncompartmental and population pharmacokinetic (popPK) models. Patients were followed up over 14 days. Efficacy variables were the mean change on thromboelastographic variables (maximum clot firmness [MCF], alpha angle [ α ]) and coagulation tests (prothrombin time, activated partial thromboplastin time, and thrombin time) 1 h postinfusion. Safety parameters were assessed. Results: Eleven patients with a median (range) age 8.80 (3.7–12.7) years were treated with the plasma-derived fibrinogen concentrate. Using the popPK modeling, fibrinogen activity reached a mean (standard deviation) C max of 1.3 (0.225) g/l, half-life ( t 1/2 ) of 60.6 (4.48) h and incremental in vivo recovery (IVR) of 1.86 (0.322) (mg/dl)/(mg/kg). Surrogate efficacy was demonstrated by significant increase in MCF (9.23 [3.94] mm; P < 0.001; 95% confidence interval 6.58, 11.87). All coagulation times were significantly shortened after fibrinogen concentrate infusion. Adverse events were mild or moderate in severity, and unrelated to fibrinogen concentrate. Conclusions: In pediatric patients with congenital afibrinogenemia, plasma-derived fibrinogen concentrate revealed a favorable and specific pharmacokinetic profile, demonstrated efficacy in coagulation and was safe and well tolerated.